1991
DOI: 10.1002/zoo.1430100503
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in the Arabian oryx (Oryx leucoryx)

Abstract: An electrophoretic survey of blood markers of the Arabian oryx (Oryx leucoryx) was undertaken in order to ascertain the genetic variability in a sample of 85 individuals, mainly from Saudi Arabian (Taif) and Jordanian herds. Three out of 18 loci were found to be polymorphic (P = 16.7%) and the mean heterozygosity (H = 0.052) appears to be relatively high with respect to the severe demographic bottlenecks expressed by the species since the 1960s. No genetic differentiation was found between Arabian and Jordania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
0
14
2
Order By: Relevance
“…Earlier, a set of 3 polymorphic loci of a protein-based fingerprinting protocol had been applied for reliable identification of sires in the Arabian oryx herd at MSPA (Vassart et al, 1991). The mean allelic polymorphism in our study was comparatively higher (3.00 versus 2.10 or 1.17, respectively) than the mean number of alleles reported earlier in microsatellite (Marshall et al, 1999) or alloenzyme (Vassart et al, 1991) based genotyping of Arabian oryx.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Earlier, a set of 3 polymorphic loci of a protein-based fingerprinting protocol had been applied for reliable identification of sires in the Arabian oryx herd at MSPA (Vassart et al, 1991). The mean allelic polymorphism in our study was comparatively higher (3.00 versus 2.10 or 1.17, respectively) than the mean number of alleles reported earlier in microsatellite (Marshall et al, 1999) or alloenzyme (Vassart et al, 1991) based genotyping of Arabian oryx.…”
Section: Discussioncontrasting
confidence: 57%
“…Earlier, a set of 3 polymorphic loci of a protein-based fingerprinting protocol had been applied for reliable identification of sires in the Arabian oryx herd at MSPA (Vassart et al, 1991). The mean allelic polymorphism in our study was comparatively higher (3.00 versus 2.10 or 1.17, respectively) than the mean number of alleles reported earlier in microsatellite (Marshall et al, 1999) or alloenzyme (Vassart et al, 1991) based genotyping of Arabian oryx. Marshall et al (1999) reported that the set of microsatellite markers they used had limited power for parentage inference due to their low allelic polymorphism however the same markers were found to be suitable for forensic use and confirmed the identity of a poached animal.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Animals forming the breeding nucleus of the NWRC herd represent a wider genetic base (Vassart et al, 1991), with the inclusion of animals derived not only from the World Herd, but also from the original Saudi, Qatari (5) and Abu Dhabi (2) genetic lineages.…”
Section: Conservation Breedingmentioning
confidence: 99%